Optimization of Air Distribution Patterns by Arrangements of ‎Air Inlets and Outlets: Case Study of an Operating Room - Vahid Gholami Motlagh; Mohammd Ahmadzadehtalatapeh (Journal of Applied and Computational Mechanics, 2022)
In this research, possible methods to improve the air distribution patterns of an operating room (OR) employing CFD method are investigated. Laminar airflow (LAF), turbulent airflow (TAF), and LAF with the air curtain are examined. It is found that LAF and LAF with the air curtain cases are superior to TAF-based cases. The study shows that the LAF and LAF with the air curtain cases as the proposed configurations have an acceptable capability to maintain the indoor air conditions within the range recommended by the standards. According to the simulations, the LAF with the air curtain case is the most suitable case in terms of the contamination risk, and it is recommended to be implemented in the existing OR.